Asbestos and lung cancer in Glasgow and the west of Scotland. Issue 6891 (5th June 1993) - De Vos Irvine, H; Lamont, D W; Hole, D J; Gillis, C R
Abstract : OBJECTIVE–To quantify the relation between lung cancer and exposure to asbestos in men in west Scotland and to estimate the proportion of lung cancer which may be attributed to exposure to asbestos. DESIGN–An ecological correlation study of the incidence of lung cancer in men and past asbestos exposure. The unit of analysis was the postcode sector. Correction was made for past cigarette smoking, air pollution, and deprivation. SETTING–The region covered by the west of Scotland cancer registry, containing 2.72 million people and including Glasgow and the lower reaches of the River Clyde, where shipbuilding was once a major industry. SUBJECTS–All men diagnosed with lung cancer between 1975 and 1984 whose residence at the time of registration was within the west of Scotland. MAIN OUTCOME MEASURE–The population attributable risk for asbestos related lung cancer. RESULTS–An estimated 5.7% (95% confidence interval 2.3 to 9.1%) of all lung cancers in men registered in the west of Scotland during the period 1975-84 were asbestos related, amounting to 1081 cases. CONCLUSIONS–A considerable proportion of cases of lung cancer in men in Glasgow and the west of Scotland from 1975 to 1984 were asbestos related. Most of these may not have been considered for compensation by the Department of Social Security. Given the very small annual number of recorded cases of asbestosis this condition is probably not a prerequisite for the development of asbestos related lung cancer. A heightened awareness of the increasing incidence of asbestos related neoplasms and their more thorough investigation are recommended.